Market Orientation of Tribhuvan University Colleges (Journal of Nepalese Business Studies, 2020)
Tribhuvan University is the largest university in Nepal. The marketing of educational services is still a debatable issue in Nepal. This study analyzes the market orientation of Tribhuvan University’s constituent colleges and affiliated colleges. The relationship among various dimensions of market orientation like customer focus, addressing student employer need, competition-oriented strategies, integration of organizational activities were examined and the impact of these dimensions was measured in terms of student satisfaction. This study is a quantitative causal analysis. Students of Tribhuvan University affiliated colleges were surveyed on the market orientation of the college. The study found that most of the colleges were not market-oriented. The study showed a positive correlation among student orientation, employer orientation and integrated activities. Further studies could analyze the market orientation of other Nepalese universities and the market orientation of particular faculty of the university.